THE IMPLEMENTATION OF CONSTITUTIONAL COURT DECISION NO. 2/PUU-XIX/2021 ON THE EXECUTION OF MOVABLE OBJECTS AS FIDUCIARY GUARANTEE - Boimau, Dibertius; Prasetyo, Dr. Dossy Iskandar; Patrianto, Dr. Bangun (jfpublisher, 2024)
Fiduciary guarantees have an important role in the implementation of credit in Indonesia, where creditors can use movable objects as collateral to ensure debt repayment by debtors. However, despite being regulated in Law No. 42/1999 on Fiduciary Guarantee, the execution of movable objects as fiduciary objects often raises legal issues, especially in relation to the protection of debtors' rights. This research focuses on the application of Constitutional Court Decision Number 2/PUU-XIX/2021 which discusses the constitutionality of Article 15 Paragraph (2) related to the execution of fiduciary guarantees. The formulation of the problems raised includes the form of legal protection for debtors against defaults committed by creditors and the mechanism for executing fiduciary guarantees. The research method used is normative juridical with a legislative approach and case studies. The results showed that the Constitutional Court's decision affirmed the creditor's right to execute the fiduciary certificate without going through the court, as long as the certificate has been registered. However, protection for debtors must still be considered, especially in the context of potential defaults from creditors. This decision strengthens legal certainty in fiduciary execution, but also demands stricter supervision to prevent abuse of power by creditors. Thus, the balance of rights between creditors and debtors can be maintained in accordance with the principles of justice in Indonesian security law.